The self-limiting nature of statin-induced rhabdomyolysis - Abdulsalam A Al-Sulaiman; Nora I Al-Muslim; Abdulaziz A Al-Quorain; Raed M Al-Sulaiman (Wolters Kluwer Medknow Publications, 2009)
Statins have come to the forefront of treatments for hyperlipidemias, coronary artery diseases and strokes. They have been shown to cause myotoxicity and rhabdomyolysis. In most cases, rhabdomyolysis is self-limiting and needs supportive therapy. Two cases of statin-induced rhabdomyolysis are reported emphasizing the definition, risk factors, clinical features and the self-limiting nature of the disorder.